The synthesis of near-infrared reflective red ceramic pigment - Rakkwamsuk, Pattana; Supothina, Sitthisuntorn; Pansukhumthana, Lada; Tangkittimasak, Teerasak (Bulletin of Applied Sciences, 2022)
This paper presents the research and development of red ceramic pigment synthesized by solid-state reaction of zircon doped with iron oxide, aluminium oxide and silicon dioxide that formed complex inorganic compound pigment. The pigment offered shades of coral red and high reflectivity in the near-infrared (NIR) region. The pigment can be used as a vehicle for a high solar reflective coating that reduces heat absorbed by building structures, promotes energy conservation in an air-conditioning system, and enhance human thermal comfort in the building. The synthesis was performed by ball-milling raw materials composed of ZrSiO4 Fe2O3 Al2O3 and SiO2. The compound of ZrSiO4 Fe2O3 Al2O3 and SiO2 at the ratio of 45:25:(30-x):x, where x varied between 0 and 30 wt%, was calcined at 1,100, 1,200 and 1,300 °C. The calcined compound was then washed, oven-dried and ground, that yielded powdered pigment with the shade of brown. The color of pigments, measured and computed in compliance with CIE L* a* b*, did not alter as the calcining temperature changed but had a brighter shade of coral red as the quantity of SiO2 increased. It was found that the pigment synthesized from ZrSiO4:Fe2O3:Al2O3:SiO2 at 45:25:20:10 and calcined at 1,100 °C offered the highest NIR reflectance at 65.9 %